#### Answer

The net change is -10

#### Work Step by Step

f(x) = 4 - 5x
Plug both 3 and 5 into the equation
f(3) = 4 - 5(3) = -11
f(5) = 4 - 5(5) = -21
Find the net change
f(5) = -21 - (-11) = -10

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

The net change is -10

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.